PENGARUH INTENSITAS PENGGUNAAN MEDIA SOSIAL TERHADAP PERILAKU KONSUMTIF MAHASISWA PRODI PENDIDIKAN EKONOMI UNIVERSITAS TANJUNGPURA - Uray Neti; Maria Ulfah; Husni Syahrudin (Universitas Tanjungpura, 2020)
AbstractThe research were to determine the intensity of the emloyment of social media within the students of the Economic Education Study Program of University Tanjungpura, the consumptive behavior of the scholars of the Economic Education Study Program of the University of Tanjungpura, and the influence of the intensity of the employment of social media on the consumptive behavior of the scholars of the Economic Education Study Program of the University of Tanjungpura. This study used a quantitative approach to causativ forms. The population was students of standard Economic Education Study Program A with a sample 65 students and uses a form. The results showed: That the intensity social media use of Regular Economics science Education Student A was categorised as high with a share of 65.2%. The level of consumptive behavior of standard Economic science Education Student A was categorised as high with a share of 69.60%. The coefficient of determination of 0.215 indicateed that the intensity of the use of social media has an effect of 21.5% on student consumptive behavior and the remaining 78.5% is influenced by other variables. Keywords: Consumptive Behavior, Intensity of Use, Social Media